A Microfluidic System for Simultaneous Raman Spectroscopy, Patch‐Clamp Electrophysiology, and Live‐Cell Imaging to Study Key Cellular Events of Single Living Cells in Response to Acute Hypoxia (Small Methods 10/2021). Issue 10 (28th October 2021) - Knoepp, Fenja; Wahl, Joel; Andersson, Anders; Kraut, Simone; Sommer, Natascha; Weissmann, Norbert; Ramser, Kerstin
Abstract : Front Cover In article number 2100470, Knoepp, Weissmann, Ramser and co‐workers developed a microfluidic device for combined laser‐based Raman spectroscopy, Patch‐clamp electrophysiology, and live cell imaging of single cells under tight oxygen‐control. This device enables the simultaneous and label‐free assessment of key cellular features underlying mammalian oxygen‐sensing processes.